2013
DOI: 10.1021/jf3042616
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Resistant Starches in Rat Cecal Contents Using Fourier Transform Infrared Photoacoustic Spectroscopy

Abstract: Fourier transform infrared photoacoustic spectroscopy (FTIR-PAS) qualitatively and quantitatively measured resistant starch (RS) in rat cecal contents. Fisher 344 rats were fed diets of 55% (w/w, dry basis) starch for 8 weeks. Cecal contents were collected from sacrificed rats. A corn starch control was compared against three RS diets. The RS diets were high-amylose corn starch (HA7), HA7 chemically modified with octenyl succinic anhydride, and stearic-acid-complexed HA7 starch. To calibrate the FTIR-PAS analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The results reported here have also been discussed in our previous publication (57). Our principal goal in this work is to develop FTIR-PAS as a practical alternative to the enzymatic assay normally used to measure starch content and demonstrate its use for multiple forms of RS.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The results reported here have also been discussed in our previous publication (57). Our principal goal in this work is to develop FTIR-PAS as a practical alternative to the enzymatic assay normally used to measure starch content and demonstrate its use for multiple forms of RS.…”
supporting
confidence: 62%
“…The ability of FTIR-PAS to detect and measure so many different factors in such a wide variety of biological materials makes it a natural choice for analysis of digesta and fecal material in dietary and disease studies, but our recent work reported here and elsewhere (57,58) appears to be the first such uses. The results reported here have also been discussed in our previous publication (57).…”
mentioning
confidence: 99%
“…It was first used by Dempster (51) and was further developed by Nier (52). Currently, EI is the most commonly used ion source utilized with GC-MS instruments.…”
Section: Electron Ionizationmentioning
confidence: 99%
“…In a companion study to this one that used the same samples, Anderson et al [52] determined through enzymatic assay that the average cecal starch content (dsb) for the control, HA7, OS-HA7, and StA-HA7 diets were 0.7, 18.3, 48.8, and 21.9 %, respectively. The residual starch differences are most likely attributed to the ability of each starch to be fermented in the cecum.…”
Section: Mass Spectrometrymentioning
confidence: 99%